Melatonin – the New Multipotential Drug of the Future? - Baranowska, Alicja; Matyka, Kamila; Matyszewska, Aleksandra; Słowiaczek, Anna; Sutkowski, Jakub; Wilczewska, Ewelina; Wojnar, Marcin (Journal of Education, Health and Sport, 2023)
Introduction: Melatonin is a well-known drug and dietary supplement that is steadily growing in popularity on the pharmaceutical market. This indolamine, which has been known for more than 50 years, is produced by the pineal gland depending on the circadian rhythm. Also referred to as the "darkness hormone" and secreted mainly during nighttime hours, it is primarily associated with the treatment of sleep-wake rhythm disorders or disorders associated with sudden shifting time zones (jet lag). However, many scientific studies have shown that melatonin has multidirectional effects. It is used both as a chronobiotic, i.e., a drug that regulates circadian rhythms, as well as having anti-inflammatory, anti-oxidative, and anti-carcinogenic properties, regulating mitochondrial function, and affecting many systems and organs, keeping the organism in a state of homeostasis. Purpose: This review article aims to provide an overview of the mechanism of action of melatonin, its current indications in clinical practice, and potential future directions for therapy use. Materials and methods: A summary of reports available in publications and scientific studies posted in medical information databases: Pubmed, CrossRef, Google Scholar, and book positions. Results: The pleiotropic effect of melatonin can be used as an supportive drug in the treatment of sleep disorders, disorders of the central nervous system, the cardiovascular system, the gastrointestinal system, and many oncological diseases. Conclusions: Despite a number of important reports on the positive effects of melatonin in the treatment of disorders in many areas of medicine, it is necessary to deepen research with its participation and the emergence of recommendations for its use in order to safely introduce the drug into common clinical practice.